Social control of egg-laying in independently nest-founding bumble bee queens - Blanca R. Peto; Claudinéia P. Costa; Meghan E. Moore; S. Hollis Woodard (BMC Ecology and Evolution)
Abstract Background Evolution has shaped diverse reproductive investment strategies, with some organisms integrating environmental cues into their reproductive decisions. In animal societies, social cues can further influence reproductive decisions in ways that might support the survival and success of the social group. Bumble bees are a lineage of eusocial insects wherein queens initiate nests independently. Bumble bee queens enter their eusocial phase only after successfully rearing their first offspring and thereafter exhibit an increased rate of egg-laying. We tested the idea that during bumble bee nest initiation, queen reproduction is socially context-dependent and under the control of social conditions in the nest. Results Our findings reveal that in the bumble bee Bombus impatiens, queen egg-laying follows a dynamic, stereotypical pattern and is also heavily influenced by social group members. During the initial stages of nest initiation, accelerated egg-laying in queens is associated with the presence of workers or older larvae and pupae. Moreover, workers are required for queens to maintain increased levels of egg laying across the nest initiation stage. We also confirmed a previously-described pattern where queens temporarily decelerate egg-laying early in nest-founding, only to increase it again when the first adult workers are soon to emerge. This “pause” in egg-laying was observed in all B. impatiens queens as well as in additional species examined. Conclusions Our results support the idea that eusocial systems can employ socially context-dependent control of queen egg-laying as a reproductive strategy. In some solitary-founding lineages, including bumble bees, queens may reach their full reproductive potential only after the emergence of the first adult workers, who then take over brood care. This stands in contrast to the hyper-reproductivity observed in some eusocial species. The presence of workers and older brood (who will soon eclose) not only alleviates queen brood care responsibilities but may also provide signals that cause queens to increase their reproductive output. These phenomena may allow queens to adapt their reproductive output to the conditions of the colony. Broadly, these findings highlight the dynamic interplay between social conditions and reproduction in bumble bees.